PEMANFAATAN SERAT PELEPAH PISANG SEBAGAI BAHAN TALI TAHAN AIR - Hasri Arlin Wuriyudani; Sulhadi Sulhadi; Teguh Darsono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Waterproof rope with diameter 5 mm and length 30 cm has been produced from banana stalk by spinning process. Spinning process is began by separating inner and outer banana fiber after drying process. The inner fiber is soaked by chitosan 2% with variation of dyeing for 1 hour to 5 hours. Chitosan 2% is obtained by dissolving acetic acid 1% with chitosan powder. Banana fiber is dried and spinned to be a rope. The quality of waterproof rope is indicated by density test, water absorption test, and breaking strength test. The highest density 0,78 is obtained from 5 hours of dyeing. The highest water absorption 87,39% is obtained without dyeing. And the breaking strength 290,00 N is obtained from two hours of dyeing. Keywords: Banana fiber, waterproof rope, chitosan